PENGARUH MOTIVASI KERJA, KERJASAMA TIM, DAN KOMITMEN TERHADAP KINERJA KARYAWAN HONORER PADA PUSKESMAS PANJI KABUPATEN SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Intan Fitriani; Mohammad Yahya Arief; Hendra Syahputra (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
As a technical implementing unit (UPT) of the Situbondo District Health Office, Panji Health Center has an important role in providing basic health services for the community in its area. The purpose of this study was to analyze and test the effect of Work Motivation, Teamwork, and Commitment on the Performance of Honorary Employees at the Panji Health Center, Situbondo Regency with Job Satisfaction as an Intervening Variable. The population in this study were honorary employees of the Panji Health Center. The sampling technique used a saturated sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the hypothesis test using the Smart PLS 3.0 application, show that Work motivation has a negative but insignificant effect on Job Satisfaction, Teamwork has a significant positive effect on Job Satisfaction, Commitment has a significant positive effect on Job Satisfaction, Work motivation has a positive but insignificant effect on Performance, Teamwork has a significant negative effect on Performance, Commitment has a positive but insignificant effect on Performance, Job satisfaction has a significant significant effect on Performance, Work motivation has a positive but insignificant effect on Performance through Job Satisfaction, Teamwork has a significant positive effect on Performance through Job Satisfaction, Commitment has a significant positive effect on Performance through Job Satisfaction.